Al-Quran dan Penciptaan Perempuan dalam Tafsir Feminis - nuraini, shinta (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2018)
This article discusses the position of women who are considered subordinate to men, the second creation and the second sex is caused by the Qur’anic interpretation about the creation of women in Surat al-Nisa 'verse 1. On this basis, feminist interpretations made by Muslim feminist figures. They are trying to straighten out the understanding of the Qur'an by reinterpreting the Qur'an which are at odds with maqashid al-shari'ah in order to uphold the egalitarian principle. This paper uses a comparative method of eight models and types of Indonesian and outside feminist interpretations both men and women. The results of this study concluded that of the eight Muslim feminists had different approaches and distinctive styles according to the interpreter's background. Although different, the feminist interpretation produces the same interpretation of Surat al-Nisa' verse 1, namely the principle of gender equality because men and women are created from the same elemental substance, namely land. The existence of both of them to complement each other.